Seasonal Variation of Heavy Metals Distribution and Sediments in Palar River in and Around Vaniyambadi Segment, Vellore District, Tamil Nadu, India - Prabhahar, C (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACT In the present investigation the levels of heavy metals in Palar River water at Vaniyambadi segment were analysed to assess the water quality. Likewise, heavy metals such as Cadmium (Cd), Chromium (Cr), Cobalt (Co), Copper (Cu), Iron (Fe), Lead (Pb), Manganese (Mn), Nickel (Ni), Strontium (Sr) and Zinc (Zn) were analysed in surface water, sediment and sediment elutriate of Palar river at Vaniyambadi segment. The sample analysis was done by microwave assisted digestion and Atomic Absorption Spectrophotometer.